Current Treatment Management of Aneurysmal Subarachnoid Hemorrhage with Prevailing Trends and Results in Tanzania: A Single-Center Experience at Muhimbili Orthopedic and Neurosurgery Institute - Waterkeyn, François; Lohkamp, Laura-Nanna; Ikwuegbuenyi, Chibuikem A; Mchome, Lemeri L; Rutabasibwa, Nicephorus B; Shabani, Hamisi K; Härtl, Roger; Petr, Ondra (World neurosurgery, 2023)
BACKGROUND: In Africa, no cerebral aneurysm treatment guidelines exist. Epidemiology, management, and outcomes after aneurysmal subarachnoid hemorrhage (aSAH) remain poorly understood, with many underdiagnosed cases. Muhimbili Orthopaedic and Neurosurgery Institute (MOI) is the only neurosurgical referral center in Tanzania. The aim of this study is to describe the current aSAH management with regional outcomes and limitations. METHODS: Patients with aSAH confirmed by computed tomography/magnetic resonance angiography between February 2019 and June 2021 were retrospectively studied. The analyzed parameters included demographics, clinical/radiologic characteristics, injury characteristics, and the modified Rankin Scale (mRS) score. RESULTS: In total, 22 patients, with a female/male ratio of 1.4 and a median age of 54 years (interquartile range [IQR], 47.2-63 years) harboring 24 aneurysms were analyzed. Thirteen patients (59.1%) paid out of pocket. The median distance traveled by patients was 537 km (IQR, 34.7-635 km). The median time between admission and treatment was 12 days (IQR, 3.2-39 days). The most common symptoms were headache (n = 20; 90.9%) and high blood pressure (n = 10; 45.4%). Nine patients (40.9%) had Fisher grade 1 and 12 (54.5%) World Federation of Neurosurgical Societies grade I. The most common aneurysms were of the middle cerebral artery (7/29.2%). Fourteen patients (63.6%) underwent clipping; of those, only 4 (28.6%) were operated on within 72 hours. Mortality was 62.5% in the nonsurgical group. Among clipped patients, 78.6% showed favorable outcomes, with no mortality. Endovascular treatment is not available in Tanzania. CONCLUSIONS: To our best knowledge, this is the first study highlighting aSAH management in Tanzania, with its assets and shortcomings. Our data show pertinent differences among international treatment guidelines, with the resultant outcomes, such as high preoperative mortality resulting from delayed/postponed treatment. Regional difficult circumstances notwithstanding, our long-term goal is to significantly improve the overall management of aSAH in Tanzania.
Keywords: Female; neurochirurgie; Neurosurgery; Tanzania; výsledek terapie; ženské pohlaví; ortopedie; lidé; Intracranial Aneurysm; Treatment Outcome; Tanzanie; subarachnoidální krvácení; retrospektivní studie; intrakraniální aneurysma; Male; lidé středního věku; Subarachnoid Hemorrhage; mužské pohlaví; Retrospective Studies; Middle Aged; Orthopedics; Humans